A new species of Clastobasis Skuse (Diptera: Mycetophilidae) from India with a world checklist - Das, Moubanti; Mukherjee, Bindarika; Pramanik, Debdeep; Naskar, Atanu; Banerjee, Dhriti (Zootaxa, 2026)
Mycetophilidae (fungus gnats) are globally distributed insects, abundant in humid woodland habitats, yet their biology and systematics remain poorly studied in many regions. Although the life histories of many Palearctic and some Neotropical species are documented, knowledge of other tropical taxa, particularly in the Oriental region, remains fragmentary. The genus Clastobasis Skuse, 1890 currently comprises 30 extant species worldwide, but only ten are known from the Oriental region, with Indian records limited to the poorly preserved Brunetti types. In this study, we describe and illustrate a new species of Clastobasis from India, supported by COX1 sequence data, representing the first DNA barcode for the genus from the country and a global checklist is also presented. This work improves the taxonomic understanding of Clastobasis in the Oriental region and contributes to the broader systematics of Leiinae.